Presence of Fasciola hepatica in Huinco. Experimental verification - Huiza F., Alina (1974)
It has been studied the presence of Fasciola hepatica L., in Huinco, place without livestock, localized in the Province of Huarochiri, Department of Lima, September 1971 and July 1972. Lymnoea viator and Physa venustula were examined looking for stages of F. hepatica and it was also performed exam of feces of the human population Iookíng for eggs of the parasite. Only L. viator snails were found infected by F. hepatica, it was confirmed with the presence of adult parasites in the biliary tract of mice infected with metacercaría obtained from L. viatar. The human infection by F. hepatica was low (0.88%). No being Huinco place for livestock, it was concluded the infection of the snails by F. hepatica could happen when the eggs arrive through the water coming from livestock places localized in higher areas than Huinco.